CONSTRUCTION AND VALIDATION OF THE MEASUREMENT INSTRUMENT OF QUALITY OF WORK LIFE BASED ON WERTHER E DAVIS THEORETICAL MODEL (Fiep Bulletin - online, 2011)
This paper aims the construction and validation of a measurement instrument of Quality of Work Life based on the Werther and Davis theoretical model. It was surveyed the criteria and sub-criteria of the Werther and Davis model, writing this indicators to the interrogative form, using a five-points Likert scale on the response scale. After that, it was realized the validation with the evaluation by researchers of the Quality of Work Life area and concluded by the instrument final version application, looking for measuring the internal consistency of the same. It concludes that was possible the creation of an specific measurement instrument of Quality of Work Life, with satisfactory psychometrics' properties, focused on organizational, environmental and behavioral elements of the task project.
Keywords: Quality of Work Life; measurement instrument; Werther and Davis model